Efficacy of Evolocumab in Patients with Hypercholesterolemia - Xuan Jin; Moo Hyun Kim; Young-Rak Cho; Jong-Sung Park; Kai Song; Song Lin Yuan (Kosin Medical Journal, 2020)
Objectives The FOURIER trial reported that inhibition of PCSK9 with evolocumab on a background of statin therapy lowered low-density lipoprotein (LDL) cholesterol levels to a median of 30 mg per deciliter (0.78 mmol per liter) and reduced the risk of cardiovascular events. Here, we report data from a single center focusing on the effect of a PCSK9 inhibitor antibody on hyperlipidemia. Methods We enrolled 29 hypercholesterolemia patients who had LDL cholesterol levels ≥ 70 mg per deciliter or non-HDL cholesterol ≥ 100 mg per deciliter and were divided into two groups (placebo n = 14, evolocumab n = 15), and participated in a 72 – 96 week, randomized, double-blind, placebo-controlled trial with statin therapy. Patients were randomly assigned to receive evolocumab (140 mg every 2 weeks or 420 mg monthly) or matched placebo via subcutaneous injection. Lipid changes during follow-up were analyzed. Results The median LDL cholesterol level at baseline was 88 mg per deciliter, and the average LDL cholesterol level was 101.8 ± 20.0 mg per deciliter. At 4 weeks, the median LDL cholesterol level was 39 mg per deciliter, and the average LDL cholesterol level was 34.8 ± 51.8 mg per deciliter. Compared to placebo group, the LDL cholesterol levels were significantly reduced after treatment (P < 0.001), as well as total cholesterol, ApoB, and ApoB/ApoA1 levels. During follow-up, no discomfort was reported at local injection sites, and no cases of abnormal liver function were observed. Conclusions Evolocumab significantly reduced LDL cholesterol levels and was well tolerated.